Facile synthesis of ZnO–Ag nanocomposite and its photocatalytic activity. (10th May 2017) - Sardar, Debasmita; Maity, Jayeta; Ghosalya, Manoj Kumar; Gopinath, Chinnakonda S; Bala, Tanushree
Abstract: The evolution of photoactive hybrid materials (e.g. noble metal-semiconductor) has resulted in heterogeneous photocatalysis. We report a facile route for the synthesis of ZnO–Ag nanocomposites with varying percentage of loading of the noble metal, expecting a great boost in the photocatalytic behavior of ZnO. The as prepared material was thoroughly characterized by UV–Vis, FTIR, TEM, FESEM, XRD, XPS analyses. The photocatalytic activities of the nanocomposites have been assessed from the ability to degrade methylene blue dye in aqueous solution. The results suggest that incorporation of Ag nanoparticles on the surface of ZnO particles can enhance catalytic activity in comparison to pure ZnO particles under visible light by minimizing the recombination of photogenerated electron–hole pairs.